The Dance of Week-End Return and Volume: A Symphony - Asnawi, Said Kelana; Pangestu, Windy; Widjaja, Caroline (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Abstract The weekend effect study is one of the studies relating to market anomalies. Research on market anomalies is important because it can be a guide for investors to transact. Concerning transactions, the TV-return pair is an appropriate indicator compared to the return itself. We use various combinations of TV-Return to find the weekend effect. The results show that mostly there is no weekend effect. Thus the efficient market hypothesis applies. This result can be a reference for investment, where Friday or Monday is no different. Investors can't beat the market